Anthropogenic CO2 emissions assessment of Nile Delta using XCO2 and SIF data from OCO-2 satellite - Ankit Shekhar; Jia Chen; Johannes C Paetzold; Florian Dietrich; Xinxu Zhao; Shrutilipi Bhattacharjee; Veronika Ruisinger; Steven C Wofsy (Environmental Research Letters, 2020)
We estimate CO _2 emissions from the Nile Delta region of Egypt, using over five years of column-averaged CO _2 dry air mole fraction (XCO _2 ) data from the NASA’s OCO-2 satellite. The Nile Delta has significant anthropogenic emissions of CO _2 from urban areas and irrigated farming. It is surrounded by the Sahara desert and the Mediterranean Sea, minimizing the confounding influence of CO _2 sources in surrounding areas. We compiled the observed spatial and temporal variations of XCO _2 in the Nile Delta region (XCO _2,del ), and found that values for XCO _2,del were on average 1.1 ppm higher than XCO _2,des (mean XCO _2 in desert area). We modelled the expected enhancements of XCO _2 over the Nile Delta based on two global CO _2 emission inventories, EDGAR and ODIAC. Modelled XCO _2 enhancements were much lower, indicating underestimation of CO _2 emissions in the Nile Delta region by mean factors of 4.5 and 3.4 for EDGAR and ODIAC, respectively. Furthermore, we captured a seasonal pattern of XCO _2 enhancement (ΔXCO _2 ), with significantly lower ΔXCO _2 during the summer agriculture season in comparison to other seasons. Additionally, we used solar-induced fluorescence (SIF) measurement from OCO-2 to understand how the CO _2 emissions are related to agricultural activities. Finally, we estimated an average emission of CO _2 from the Nile Delta from 2014–2019 of 470 Mt CO _2 /year, about 1% of global anthropogenic emissions, which is significantly more than estimated hitherto.